EFFECTS OF IMPLEMENTATION OF WATER-SAVING IRRIGATION TECHNOLOGIES IN COTTON GROWING ON SOIL SALINITY REGIME (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article discusses the impact of water-saving technologies on soil salinity during the cultivation of the "Bukhara-8" variety in the conditions of the Bukhara region. During the experiments, it can be seen that the amount of salts in the soil is relatively low and a favorable environment is created for the growth of the plant in the case of watering cotton by laying a black polyethylene film on the soil.